Comparison of a fungal (family I) and bacterial (family II) cellulose-binding domain. - Tomme, P (1995)
A family II cellulose-binding domain (CBD) of an exoglucanase/xylanase (Cex) from the bacterium Cellulomonas fimi was replaced with the family I CBD of cellobiohydrolase I (CbhI) from the fungus Trichoderma reesei. Expression of the hybrid gene in Escherichia coli yielded up to 50 mg of the hybrid protein, CexCBDCbhI, per liter of culture supernatant. The hybrid was purified to homogeneity by affinity chromatography on cellulose. The relative association constants (Kr) for the binding of Cex, CexCBDCbhI, the catalytic domain of Cex (p33), and CbhI to bacterial microcrystalline cellulose (BMCC) were 14.9, 7.8, 0.8, and 10.6 liters g-1, respectively. Cex and CexCBDCbhI had similar substrate specificities and similar activities on crystalline and amorphous cellulose. Both released predominantly cellobiose and cellotriose from amorphous cellulose. CexCBDCbhI was two to three times less active than Cex on BMCC, but significantly more active than Cex on soluble cellulose and on xylan. Unlike Cex, the hybrid protein neither bound to alpha-chitin nor released small particles from dewaxed cotton fibers.